Hemiplejía aguda infantil. - García Tigera, Jorge; Bender del Busto, Juan E.; Pérez Pérez, Oscar; Sardiñas Hernández, Norberto; Rojas Massip, Edelsia (Revista Cubana de Pediatría, 2023)
Se analiza la casuística del Instituto Nacional de Neurología durante 20 años.